Modeling the effect of modified local polymer on the rheological and filtration properties of water-based drilling fluid (2021)
In order to achieve a successful drilling operation, the drilling fluid used must be properly designed. Water based drilling muds that are formulated to suit drilling requirements include additives like clays for higher viscosity and starch for better filtration control properties. Locally available yams (Dioscorea) are a good source of starch, with good absorbent properties that give its good filtration control properties but poor gelling properties due to the easily soluble branched chained Amylopectin molecules which causes it to easily degrade. While mud samples treated with Carboxylmethyl cellulose (CMC) was used as control. Chemical modification of starch has been researched to be a good method of improving its gelling properties in water based mud which in turn improves the rheological properties of the mud. Cross linking agents like sodium acetate and ammonium phosphate are used to cross-link the Amylopectin and Amylose molecules in the starch thus making them less degradable. An experimental study was carried out to reduce the yams starch bio-degradable nature via chemical modification with some cross-linking agents (sodium acetate and ammonium phosphate). The results from the rheological and filtration control test carried out on the formulated mud samples treated with modified yams starch additive gave higher gel strength and yield point, exceptional shear thinning ability, lower plastic viscosity and a good but lower fluid loss control when compared to with the control samples. A Factorial design was developed to predict the rheological properties of the mud system at different temperatures and varying starch quantities. The results of the mud samples treated with the non-modified starches, modified yam starches and imported viscosifier (CMC) are indicators that the modified starches improved its gelling nature thereby giving the drilling mud a better rheological properties.